2022
DOI: 10.1111/josi.12537
|View full text |Cite
|
Sign up to set email alerts
|

“You are stealing our present”: Younger people's ageism towards older people predicts attitude towards age‐based COVID‐19 restriction measures

Abstract: The COVID‐19 pandemic emerged to be a fertile ground for age‐based prejudice and discrimination. In particular, a growing literature investigated ageism towards older people at the individual and the interpersonal level, providing evidence of its prevalence, antecedents and negative consequences. However, less much is known on the phenomenon at the intergroup level. To fill this gap, the present correlational research investigated the effects of younger people's endorsement of ageism towards older people on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 95 publications
2
27
0
Order By: Relevance
“…This, in turn, impacted people's well-being, increased the risk of suicidal behaviour (see Hafford-Letchfield et al, 2022), and increased risk of financial crisis (see also Lytle & Levy, 2022;McDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022). Whilst some studies reported that participants maintained their social contacts, others mentioned the quantity and quality of social contacts deteriorated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, impacted people's well-being, increased the risk of suicidal behaviour (see Hafford-Letchfield et al, 2022), and increased risk of financial crisis (see also Lytle & Levy, 2022;McDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022). Whilst some studies reported that participants maintained their social contacts, others mentioned the quantity and quality of social contacts deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research highlights that the COVID-19 health and safety measures have led to increased mental health problems, such as increased feelings of depression, anxiety, social isolation, and loneliness, potentially cognitive decline (Allen et al 2021;Bailey et al, 2021;Dahlberg, 2021;Derrer-Merk et al, 2022b;Derrer-Merk et al, 2022a;Heidinger & Richter, 2020;Richter & Heidinger, 2021;Krendl & Perry, 2021;Litwin & Levinsky, 2021;De Pue et al 2021;Shahid et al, 2020;Smith et al, 2020;Cohn-Schwartz et al, 2022;Tsoukalis-Chaikalis et al, 2021;van Gerwen et al, 2021;Victor et al, 2022;Vrach &Tomar, 2020). Other studies reported the consequences of age discrimination (Derrer-Merk et al, 2022c;Lytle & Levy, 2022;MCDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022;Sutter et al, 2022;Swift & Chasteen, 2021;). Risk communication and how it is perceived by society are also important aspects of risk management in a pandemic such as COVID-19 (Sandman, 2003(Sandman, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, age stereotyping and prejudice have become more negative (Ng et al., 2015 ), with ageist views noticeably heightened during the global COVID‐19 pandemic (Spaccatini et al., 2022 ). Older adults have been disproportionately affected by social isolation (e.g., Derrer‐Merk et al., 2022 ) as well‐intentioned officials emphasized the frailty of older adults and issued stay‐at‐home orders specific to older age groups (Hwang et al., 2020 ).…”
Section: Background and Aimsmentioning
confidence: 99%
“…Apriceno et al [ 16 ], in turn, found that, among American undergraduates, hostile ageism was associated with lower ratings of prioritizing older people in getting COVID-19 triage, testing, and vaccine, while benevolent ageism was positively associated with higher priority ratings. Focusing on intergenerational tensions, Spaccatini et al [ 36 ] ran an online survey among young Italian respondents assessing ageism, attributions of culpability for the severity of COVID-19 restrictions to older people, and attitudes toward the selective isolation of older (but not young) people and selective lockdown of older people. They found that ageism was positively associated with attributions of culpability to older people for the severity of COVID-19 restrictions, and consequently with support for isolation and lockdown for older people only.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, previous research analyzing associations between ageism and attitudes and behaviors during the pandemic has consistently found undesirable effects of unfavorable attitude toward older people and hostile ageism which were associated with lower preventive behaviors [ 13 , 14 , 15 ], reduced helping behaviors [ 30 ], and beliefs that older people should not be prioritized in COVID-19 treatment [ 16 ] or should be isolated during the pandemic [ 36 ]. The effects of benevolent ageism on attitudes and behaviors during the pandemic are instead less consistent [ 13 , 14 , 15 , 16 , 35 ].…”
Section: Introductionmentioning
confidence: 99%